2006
DOI: 10.1111/j.1365-2966.2006.10507.x
|View full text |Cite
|
Sign up to set email alerts
|

HST/STIS optical spectroscopy of five super star clusters in the starburst galaxy M82

Abstract: We present optical spectroscopy obtained with the Space Telescope Imaging Spectrograph of five young massive star clusters in the starburst galaxy M82. A detailed analysis is performed for one cluster ‘M82‐A1’ and its immediate environment in the starburst core. From Hubble Space Telescope archive images, we find that it is elliptical with an effective radius of 3.0 ± 0.5 pc and is surrounded by a compact (r= 4.5 ± 0.5 pc) H ii region. We determine the age and reddening of M82‐A1 using synthetic spectra from p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
156
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(170 citation statements)
references
References 50 publications
(115 reference statements)
13
156
1
Order By: Relevance
“…However, as noted by Silich et al (2007), this cannot be the whole story. The observed properties of the H ii region associated with the massive (1.3 × 10 6 M ), young (age ∼ 6 Myr) and thus powerful (with a mechanical luminosity, L mech ≈ 2.5×10 40 erg s −1 ) SSC M82-A1 (Smith et al 2006) are 932 SILICH ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…However, as noted by Silich et al (2007), this cannot be the whole story. The observed properties of the H ii region associated with the massive (1.3 × 10 6 M ), young (age ∼ 6 Myr) and thus powerful (with a mechanical luminosity, L mech ≈ 2.5×10 40 erg s −1 ) SSC M82-A1 (Smith et al 2006) are 932 SILICH ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…The large central temperature depressions at the critical line and the slow acceleration of the reinserted matter within the cluster are indicative of the last stationary solution found before crossing the critical line. The presence of dust in the thermalized plasma within young SSCs provides a natural explanation for the observational and theoretical studies that have derived a strongly reduced mechanical energy output from some of the massive clusters in the galaxy M82 in order to account for the size of the compact H ii regions that surround them (see Smith et al 2006;Silich et al 2007Silich et al , 2009. Further evidence for the bimodal solution and the positive star formation feedback may come from the interpretation of the abundance variations from star to star in massive globular clusters (GC), such as ω Cen in the Milky Way where different generations of stars are enriched by different contributors, and among these by core-collapse SNe (Gratton et al 2004) or from observations of the most massive GCs in M31 where the run of α to Fe-peak elements is consistent with a primordial enrichment from stars with masses larger than 10 M (Meylan et al 2001).…”
Section: Strong Radiative Cooling and The Location Of The Threshold Linementioning
confidence: 99%
“…Subsequent studies of the stellar fossil record in M82 have since found evidence of widespread elevated levels of star-forming activity roughly 0.5-1 Gyr in the past (e.g., de Grijs et al 2001;Mayya et al 2006). More recent episodes of star-forming activity have been restricted to the inner regions of M82 (e.g., Gallagher & Smith 1999;Forster Schreiber et al 2003;Smith et al 2006).…”
Section: Introductionmentioning
confidence: 99%